1999
DOI: 10.1073/pnas.96.5.2408
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa killing of Caenorhabditis elegans used to identify P. aeruginosa virulence factors

Abstract: We reported recently that the human opportunistic pathogen Pseudomonas aeruginosa strain PA14 kills Caenorhabditis elegans and that many P. aeruginosa virulence factors (genes) required for maximum virulence in mouse pathogenicity are also required for maximum killing of C. elegans. Here we report that among eight P. aeruginosa PA14 TnphoA mutants isolated that exhibited reduced killing of C. elegans, at least five also exhibited reduced virulence in mice. Three of the TnphoA mutants corresponded to the known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
519
4
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 562 publications
(548 citation statements)
references
References 40 publications
16
519
4
4
Order By: Relevance
“…Slow killing P. aeruginosa assays were performed using the P. aeruginosa strain as described (Tan et al, 1999). All assays performed using L4 or young adult stage hermaphrodites, unless noted.…”
Section: Worm Stress and Life Span Assaysmentioning
confidence: 99%
“…Slow killing P. aeruginosa assays were performed using the P. aeruginosa strain as described (Tan et al, 1999). All assays performed using L4 or young adult stage hermaphrodites, unless noted.…”
Section: Worm Stress and Life Span Assaysmentioning
confidence: 99%
“…It has become apparent, however, that this is not always the case. For example, P. aeruginosa QS systems have been demonstrated to be important for pathogenesis in multiple animal infection models (325)(326)(327)(328), and AHLs and QS-regulated genes have been demonstrated to be expressed in vivo (329)(330)(331). However, analyses of clinical P. aeruginosa isolates have revealed that lasR, and less frequently rhlR, can be mutated during infection (332)(333)(334)(335)(336).…”
Section: Concernsmentioning
confidence: 99%
“…aeruginosa virulence has been shown in numerous model systems. These include the Caenorhabditis elegans model (Tan et al, 1999), the acute pneumonia model (Pearson et al, 2000), and the chronic pneumonia agar bead model (Wu et al, 2001). Since the absence of quorum sensing reduced virulence in all models, including the lung model, we believed that quorum sensing may likewise affect the severity of prostate disease.…”
Section: Introductionmentioning
confidence: 99%